Audio-Visual Tools in Science Communication: The Video Abstract in Ecology and Environmental Sciences - Ferreira, Miguel; Lopes, Betina; Granado, António; Freitas, Helena; Loureiro, João (Frontiers in Communication, 2021)
In recent years, the use of videos by the scientific community has evolved continuously. Researchers, communicators, and other players are using audio-visual media to reinvent their stories, to deconstruct complex phenomena and to increase the outreach and impact of their scientific publications. An example of this trend is the video abstract: an audio-visual representation of the key findings described in the written abstract. Much of the research in this area is new and focused on content analysis and classification of online science videos. Furthermore, studies with videos and environmental communication are attached to specific topics like climate change. So far, a small fraction of publications has explored the study of the video abstract, its effects, and its potential, as one general scientific area. This paper provides the first characterization of video abstracts in the areas of Ecology and Environmental Sciences. We identified video abstracts in 29 scientific journals, based on impact, representativeness and visibility criteria. A database of 171 videos, from 7 publishers and 17 different video channels was created. Each video was analysed for different parameters. The analysis considered not only characteristics of each video, but also characteristics from the corresponding scientific papers. Results indicate that between 2010 and 2018 the number of video abstracts increased sevenfold. Despite this growth, there was no solid strategy for disseminating the videos. While most of them are still associated with classic models, such as documentaries, disruptive formats such as animation are the ones that arouse greater interest. Professional shorter videos (2-3 minutes in length) showed a significantly higher number of daily views and their papers garnered a higher number of citations per day. This data, combined with future qualitative research, will help to develop a model for validating the quality of an Ecology video abstract and provide new insights into the global study of audio-visual communication of science.